Pengaruh Ekspor Dan Impor Terhadap Cadangan Devisa Tahun 2018-2022 - Rosmay Kumala; Ani Rakhmanita (Peneliti.net, 2023)
Export and import activities are carried out so that a country and other countries need each other's assistance and complement each other. in carrying out export and import activities to other countries requires foreign exchange reserves. The purpose of this study is to determine the effect of exports and imports on Indonesia's foreign exchange reserves in 2018-2022. The research method used is a quantitative method. This study uses secondary data obtained from the Central Statistics Agency (BPS) and Bank Indonesia (BI) with a data collection method, namely documentation techniques. The analytical method used in this study uses hypothesis testing, classic assumption testing and multiple linear analysis using the time series method for 5 years from 2018-2022 and processing data using SPSS software. The results of the study show that the (partial) T test can show that exports as (X1) have a significant effect on Indonesia's foreign exchange reserves in 2018-2022 and imports as (X2) have no effect on Indonesia's foreign exchange reserves in 2018-2022. Meanwhile, based on the F (simultaneous) test, the two independent variables simultaneously have a significant influence on Indonesia's foreign exchange reserves in 2018-2022.